Women shy away from competition: How to overcome it - Amanda H. Goodall; Margit Osterloh; Mandy Fong (Center for Research in Economics, Management and the Arts (CREMA), 2020)
Women remain underrepresented at the upper echelons. An aversion to competition has been suggested as a factor that discourages women from applying for top jobs. This paper reviews the research showing that high-ability females compete less than males. We develop a theoretical approach to explore why there are gender differences in competitive behaviours and identify flaws in the current recruitment methods, which constrain the supply of qualified candidates. On this basis, we discuss two policy implications that may mitigate competitiveness and thereby motivate high-ability women to apply for leadership positions. The first is quotas. Next we introduce an innovative tool that has a long yet little-known history - focussed random selection from a pre-chosen pool of candidates. We suggest this as a way to contribute to closing the gender gap in competitiveness and enlarging the pool of high-performing women applying for top jobs.
Keywords: 330; Competitive behaviour; focussed random selection; gender stereotypes; leadership